2019
DOI: 10.18203/issn.2454-2156.intjscirep20190642
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of diaphyseal fractures of forearm in adolescents treated with TENS

Abstract: <p class="abstract"><strong>Background:</strong> A retrospective case series study was done on forearm diaphyseal fracture in adolescents treated with TENS (titanium elastic nailing system). Purpose of the study was analysis of functional outcome of TENS in forearm diaphyseal fractures in children between 12-18 year age group.</p><p class="abstract"><strong>Methods:</strong> We retrospectively evaluated 30 patients operated by same senior surgeon during the period from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…14 Our study had a male predominance, with 18 (66.7%) cases being male patients. Similar male predominance was observed in other studies, such as the one by Goyal et al, 10 which had 21 male and 9 female cases, as well as in the studies by Naorem et The most common mode of injury in our study was a fall on an outstretched hand, accounting for 70.4% of cases, followed by 22.2% due to road traffic accidents and 7.4% due to other modes of injury, such as a direct blow to the forearm or a natural fall from height. Similar findings were reported in the study by Vopat et al, 1 where a fall on an outstretched hand was the most common mode of injury in 83% of cases, and in the study by Kruppa et al, 17 where a fall on the hand accounted for 98% of cases.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…14 Our study had a male predominance, with 18 (66.7%) cases being male patients. Similar male predominance was observed in other studies, such as the one by Goyal et al, 10 which had 21 male and 9 female cases, as well as in the studies by Naorem et The most common mode of injury in our study was a fall on an outstretched hand, accounting for 70.4% of cases, followed by 22.2% due to road traffic accidents and 7.4% due to other modes of injury, such as a direct blow to the forearm or a natural fall from height. Similar findings were reported in the study by Vopat et al, 1 where a fall on an outstretched hand was the most common mode of injury in 83% of cases, and in the study by Kruppa et al, 17 where a fall on the hand accounted for 98% of cases.…”
Section: Resultssupporting
confidence: 90%
“…The prospective clinical study was conducted in the Department of Orthopaedics, B.P. Koirala Institute of Health Sciences, Nepal, between December Goyal et al (2019), who observed that 80% of the patients undergoing TENS fixation achieved excellent functional outcomes. 10 Considering P (proportion) =80% Q (complement of P) =100-p=20% L (Permissible error) =20% of P=16 By Formula: Sample size (n) = Z 2 PQ/L 2 , where Z (95% confidence level) =1.96 = 24.01 = 24…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, there were excellent outcomes in 91%, good outcomes in 6.4% and fair results in only 2.6% of patients based on Prince criteria. 29 Likewise, study of Goyal D et al 30 demonstrated that TENs has overall good to excellent results in adolescent forearm fractures provided the principle of three point fixation was followed and soft tissue injury was minimal.…”
Section: Discussionmentioning
confidence: 98%
“…13 Regarding gender distribution, approximately two-thirds of participants (67%) were male, aligning with similar findings in another study. 14 Analyzing the type of injury, the majority of participants (91%) had simple/closed injuries, while 9% had compound/open injuries. On the contrary, we noted that right-side involvement (61%) was higher than leftside involvement (39%) among participants.…”
Section: Discussionmentioning
confidence: 99%